¿Qué se espera de los docentes en la Innovación Curricular? - Depaux V., Ruth (Revista Hospital Clínico Universidad de Chile, 2014)
This article first rewiews the basis and principles that support curriculum innovation. Keeping this in mind, the role teachers must play in this process, becomes clear almost spontaneously.